Policies and Interventions to Provide Safety for Pedestrians and Overcome the Systematic Biases Underlying the Failures - Job, Raymond Franklin Soames (Frontiers in Sustainable Cities, 2020)
Road transport is failing pedestrians more than other road users. For pedestrians, roads are not safe or improving: Globally pedestrian deaths have increased at nearly twice the rate of other road crash deaths (12.9% increase from 2013 to 2016, versus a 6.6% increase for other road users). Pedestrians commonly lack safe crossings, safe speeds, and in many locations, footpaths. This paper briefly identifies successes and failures for pedestrian safety, reviews weaknesses and limitations to actions for pedestrian safety and identifies barriers to effective action. Barriers include current culture on road usage, victim blaming, under-estimation of the pedestrian crash death problem in particular, and other crash data issues. Advocacy, policies and actions are recommended to overcome these barriers and to improve pedestrian safety.